1996
DOI: 10.1248/bpb.19.157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carnitine on Decrease of Branched Chain Amino Acids and Glutamine in Serum of Septic Rats.

Abstract: Blood concentrations of branched chain amino acids (BCAA; leucine, isoleucine, and valine) and glutamine (Gln) decrease markedly in sepsis. We investigated the effect of carnitine on serum concentrations of BCAA and Gln in fasted septic rats. Rats were made septic by cecal ligation and puncture. They developed extremely high blood concentrations of endotoxin, and serum concentrations of BCAA and Gln were markedly decreased 2 d after the operation. When L-carnitine was administered subcutaneously to the rats at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is suggested that glutamine catabolism decreased because more fat was available for energy production. Glutamine has been suggested to be a key fuel for the intestinal mucosa and essential substrate for other rapidly dividing cells such as lymphocytes; glutamine concentration is reduced when protein is the main source of energy (Ardawi 1988; Lacey and Wilmore 1990; Hayashi et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that glutamine catabolism decreased because more fat was available for energy production. Glutamine has been suggested to be a key fuel for the intestinal mucosa and essential substrate for other rapidly dividing cells such as lymphocytes; glutamine concentration is reduced when protein is the main source of energy (Ardawi 1988; Lacey and Wilmore 1990; Hayashi et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Postprandially, branched-chain amino acids (BCAA: leucine, isoleucine, and valine) and glutamine are strongly catabolized (Lacey and Wilmore 1990). Hayashi et al (1996) observed that L L-carnitine treatment prevented a decrease of serum concentrations of BCAA and glutamine in septic animals, sepsis being associated with suppression of fatty acid and glucose oxidation. In the present study, BCAA were found at lower levels in carcasses from fish that had not been supplemented with extra L L-carnitine.…”
Section: Body Amino Acid Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…In septic rats that had undergone appendix ligation and perforation, the concentration of endotoxins in the blood rose, while the concentrations of branched chain amino acids in the blood (leucine, isoleucine and valine) as well as glutamine were lower. Administration of L-carnitine, however, is shown to suppress declines in the concentrations of branched-chain amino acids and glutamine [ 17 ]. Aged rats, in particular, show decreases in the content of protein in each tissue as well as the level of protein-bound hexose, hexosamine, sialic acid, and fucose.…”
Section: Discussionmentioning
confidence: 99%